Two-fluid Numerical Simulations of the Origin of the Fast Solar Wind - Wójcik, D.; Kuźma, B.; Murawski, K.; Srivastava, A.K. (Institute of Physics Publishing, 2019)
With the use of our JOANNA code, which solves radiative equations for ion + electron and neutral fluids, we perform realistic 2.5D numerical simulations of plasma outflows associated with the solar granulation. These outflows exhibit physical quantities that are consistent, to the order of magnitude, with the observational findings for mass and energy losses in the upper chromosphere, transition region, and inner corona, and they may originate the fast solar wind. © 2019. The American Astronomical Society. All rights reserved..
Keywords: magnetohydrodynamics (MHD) – methods; numerical – solar wind – Sun; activity – Sun; corona